Impact of VUCA world on children’s emotional development during online learning - Afiq Azri Mohd Ghani; Lim Seong Pek; Rita Wong Mee Mee; Md Rosli Ismail; Fatin Syamilah Che Yob; Uzzairah Nabila Ahmad Tazli; Tengku Shahrom Tengku Shahdan (International Journal of Public Health Science (IJPHS), 2022)
Living in a world of unstable and fluctuating economy has put children’s development at risk particularly children from low-income families. Hence their development should be on alert. The concern regarding online learning is crucial towards children’s emotional development as it can positively or negatively affect them. In the volatility, uncertainty, complexity, and ambiguity (VUCA), no other performance is relevant due to high-speed change. Children as young generations today have more disruptive behaviours causing adults to be fearful in dealing with their unruly behaviour. This study discovered the impact of the current environmental situation of uncertainty and parent-child relationship on children’s emotional development. In view of the COVID-19 pandemic restrictions and preventive measures, the study was conducted with parents’ consent using an online survey tool administered using Google Form. The quantitative survey comprised general population-CORE (GP-CORE) and perceived stress scale (PSS) questionnaires from 108 respondents studying in primary schools around urban areas in Selangor, Malaysia. The findings were analysed and described descriptively. Findings showed that children are greatly affected by parents’ job loss and low-income households’ instability, causing emotional stress when learning from home. Therefore, the study can be the mechanism to aid the educational system in emphasising emotional learning in school.